Nominalism, Thomism, Scotism: Seeds of Modern Science in Medieval Philosophy (International Journal of World Civilizations and Philosophical Studies, 2025)
The development of modern science is often portrayed as a radical departure from medieval thought, yet this this perspective overlooks the significant contribution of medieval philosophy to scientific revolution. This explores how three major philosophical schools such as Nominalism, Thomism, and Scotism, did laid the intellectual groundwork for early modern scientific inquiry. By examining the philosophical debates surrounding universals, empirical observation, the harmonizing of faith and reason, this study highlights how these traditions fostered a culture of critical thinking and intellectual openness that nurtured scientific progress. Nominalism emphasis on observation and skepticism of universals, encouraged the development of empirical methods, Thomism structured reasoning provided logical frameworks for organizing scientific knowledge, and scoticism's focusing on contigency allowed for alternative explanations of natural phenomena. Drawing on historical secondary sources, this paper demonstrates these philosophical schools not only influenced renowned figures like Copernicus, Kepler, and Galileo but also shaped broader intellectual trends in mechanics, optics, and cosmology. Ultimately, the study argues that medieval thought played an essential role in the gradual evolution of philosophical ideas that led to the flourishing of modern science, challenging the traditional narrative of a sharp break between the medieval and modern periods.